Mediações e produção de sentidos em políticas de currículo: os contextos de construção da política de ciclo na experiência da Escola Cabana (1997/2004) - Barreto, Edna Abreu (2009)
This study analyses the experience of the curriculum reorientation of the cycle policy for the ensino fundamental (elementary + middle school) in Belém city, Pará state, Brazil, during two consecutive terms of the municipal government (1997-2000 and 2000-2004), and attempts to understand the mediations and the possible hybrid meanings of the texts and discourses produced in this curriculum policy. This work is part of the analyses proposed by the field of curriculum, and its theoretical perspective considered the curriculum as a cultural policy, where disputes for meaning and the production of certain symbolic developments are at stake. The theoretical reference that subsidized my analysis drew from the concept of continuous policy cycle, formulated by Professor Stephen Ball, an English researcher. Highlighting the complex and controversial nature of the educational policy, his theory proposes the existence of a continuous policy cycle that comprises five contexts: the influence context, the context of text production, the practice context, the context of results, and the context of political strategy. I analyzed the documents, considering the curriculum texts as complex processes that involve their production, breaking with the analyses that treat the official documents as exclusive elaborations of government, while practices are the setting for the implementation of these official discourses, or a rebellion against them. The methodology used came from the contributions of qualitative research in education, and the documents were analyzed according to the texts complexity and the discourses produced by the cycle policy of Cabana School. In the empirical analysis of the documents, I considered the educational policy as discourses and texts simultaneously. I interviewed one of the technicians who participated in the cabana school management on an open and flexible basis, aiming to understand the production process and the documents presentation to the municipal school system. Analyzing the contexts of influence and production of texts of the cycle policy, as proposed in the policies cycle, I argued that the course of these texts construction, consolidated during the eight-year term of cabana school management, turned from a restrictive discourse, in relation to the practice context, to another type of discourse now more open and likely to allow different readings. This course was gradually altered along the policy building although, on many occasions, it is possible to notice there was an attempt to restrict the senses of practice. Finally, I considered that understanding the undetermined aspect of the curriculum policies can enlarge the possibilities of analysis since one considers the plurality of the processes that involve the production of the curriculum policies in the diffuse context of the contemporary culture.